2017
DOI: 10.11604/pamj.2017.26.140.10345
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcome of traumatic brain injury patients at Muhimbili Orthopaedic Institute Dar es Salaam, Tanzania

Abstract: IntroductionTraumatic brain Injuries represents a significant cause of morbidity and mortality worldwide and road traffic crashes accounts for a significant proportion of these injuries. However, access to neurosurgical care is poor in low income countries like Tanzania. The aim of this study was to assess the management and outcome of Traumatic brain injury patients at a tertiary level health facility in Tanzania.MethodsA retrospective observational study of Traumatic brain injury patients attended at Muhimbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 19 publications
5
35
1
Order By: Relevance
“…In comparable studies originating from high-income countries the use of CT scan amounts to 87% of all trauma cases [ 37 ]. A previous study in Tanzania showed high user fee-cost and the low knowledge of traumatic-brain-injury protocols among the providers limited a wider utilization of CT scan, which may contribute to the low usage rates [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparable studies originating from high-income countries the use of CT scan amounts to 87% of all trauma cases [ 37 ]. A previous study in Tanzania showed high user fee-cost and the low knowledge of traumatic-brain-injury protocols among the providers limited a wider utilization of CT scan, which may contribute to the low usage rates [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Kigali, TBIs were most commonly caused by RTIs, which is similar to prior studies from neighboring countries. 6,20 Other Sub-Saharan African countries, however, have reported lower rates of head injuries associated with RTIs. 5 A possible cause for the high incidence reported in the study is the rapid urbanization of Kigali, which is bringing more vehicles onto the road.…”
Section: Discussionmentioning
confidence: 99%
“…5 Road traffic crashes were the leading cause of TBI in Tanzania (59%). 6 In Kigali, the capital city of Rwanda, TBIs are responsible for approximately 16% of injuries presenting to the University Teaching Hospital of Kigali (CHUK), with severe TBI patients having a mortality rate as high as 58%. 7,8 This made head injury the most common diagnosis in injury-related deaths in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…One study at a large tertiary hospital in Malawi found 18% of admitted trauma patients had a TBI with a 30% mortality rate for all TBI [ 9 ]. A retrospective analysis at a tertiary hospital in Tanzania reported 56% of TBIs were due to road traffic incidents with 17.8% of TBI patients classified as severe and a 30.7% mortality rate [ 10 ]. A retrospective review of over ten-thousand injured patients presenting to tertiary hospitals in Western Cape, South Africa identified TBI in 24% of injured patients; 27% of these TBIs were moderate to severe and required admission [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgery was indicated for 15% of patients who had a CT scan and medical treatment was changed in an additional 18% [ 12 ]. The majority of TBI patients are young males (average age range 28.8-38.8 years), with the majority of TBI originating from road traffic incidents, interpersonal violence, and falls [ 1 , 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%